2021
DOI: 10.3389/fcvm.2021.691907
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Outcome in Patients Treated With SGLT2 Inhibitors for Heart Failure: A Meta-Analysis

Abstract: Background: Sodium–glucose co-transporter 2 (SGLT2) inhibitors are an emerging class of glucose-lowering drugs that have become increasingly relevant for the treatment and prevention of heart failure (HF). Therefore, we aimed to investigate various SGLT2 inhibitors in patients with established HF at baseline and focused on the different types of HF.Methods: An extensive search of PubMed and Web of Science until January 2021 was done. Two reviewers, independently and in duplicate, applied the selection criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 65 publications
0
30
0
1
Order By: Relevance
“…In summary, based on the findings from the meta-analysis of Gager et al (1) and ours, SGLT2 inhibitors should be recommended in a broad population of patients with HF patients, those with diabetes or not, those with reduced eGFR or not, and those with preserved/reduced LVEF. Moreover, SGLT2 inhibitors should be more recommended in Asian and Black patients with HF and patients with HF and with NYHA class II because of the greater benefits of this drug class in these HF subpopulations.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…In summary, based on the findings from the meta-analysis of Gager et al (1) and ours, SGLT2 inhibitors should be recommended in a broad population of patients with HF patients, those with diabetes or not, those with reduced eGFR or not, and those with preserved/reduced LVEF. Moreover, SGLT2 inhibitors should be more recommended in Asian and Black patients with HF and patients with HF and with NYHA class II because of the greater benefits of this drug class in these HF subpopulations.…”
Section: Discussionmentioning
confidence: 70%
“…The meta-analysis of Gager et al ( 1 ) confirmed the consistent efficacy of SGLT2 inhibitors on the composite HF outcome (i.e., a composite of HHF/CVM) in various HF subgroups defined by several important factors, such as baseline diabetes status, type of SGLT2 inhibitors, and baseline level of eGFR. However, Gager et al ( 1 ) failed to perform subgroup analyses according to three other important factors: region, race, and baseline NYHA class. Thus, their findings ( 1 ) could not guide whether SGLT2 inhibitors should be used in patients with HF patients living in a specific region, those with a specific race, or those with a specific NYHA class.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations